Surface modification of flat cable conductors: a path to withstand the aggressive space environment - Kleiman, Jacob; Iskanderova, Zelina (Mechanics and Advanced Technologies, 2020)
A novel ion-beam surface treatment process with simultaneous surface renewal (IB/SSR) providing charge-dissipative properties to the treated surfaces was developed at ITL and successfully used for treatment of both sides of variously shaped and sized flat conductor cables (FCC) that are being used in various applications in aerospace, space and commercial programs. The results of surface resistivity (SR) measurements of the front side of FCC’s used as interconnects in solar panel arrays on satellites in Geostationary (GEO) orbit averaged around 10 MΩ/sq for short FCC units and around 8 MΩ/sq for long units. The SR values for back sides averaged around 18 MΩ/sq for both short and long FCCs. These values remained unchanged during ~ 1 month storage of the treated FCCs at lab conditions, and after a following 2-2.5 year’s storage. Extended long-term ground-based GEO environment simulation testing experiments (15 years space equivalent) that involved simultaneous exposure to all three GEO environmental factors, i.e. protons, electrons, and UV have been performed on two specially selected FCC sets. These sets included pristine and IB/SSR-treated FCCs, with both front and back FCC surfaces being exposed. It was demonstrated that the surface conductivity obtained on the insulating space polymer films is almost insensitive to space radiation during the 15 years in GEO. It was also shown that the long-term influence of GEO radiation on thermal optical characteristics of both FCCs sides does not significantly differ for pristine and ion-beam treated samples.